Administrative Management: E-Buddy Implementation Constraints in Rangkah Kidul Village: Manajemen Administrasi: Kendala Implementasi E-Buddy di Desa Rangkah Kidul - Trias, Hermin Oknanin; Mursyidah, Lailu (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The mandate for Electronic-Based Government System (SPBE) requires all government levels, including villages, to adopt E-Office applications to enhance efficiency and public services. Specific Background: This study focuses on the implementation of the E-Buddy application in the Rangkah Kidul Village Government for administrative management. Knowledge Gap: Existing literature lacks specific evaluation of E-Office implementation success factors at the micro (village) level using established implementation models. Aims: To analyze and describe the E-Buddy application’s implementation based on Merilee S. Grindle’s four indicators: Communication, Resources, Disposition, and Bureaucratic Structure. Results: Implementation has not fully met the criteria. Communication is quite good but lacks consistent information delivery. Resources (officer capability) and Disposition (officer commitment) are major constraints, as several officials are unable to operate E-Buddy optimally. Bureaucratic Structure is supportive, aligned with Sidoarjo Regent Regulation No. 30/2020. Novelty: Applying Grindle's model identifies human factors and capacity gaps as the primary implementation obstacles for E-Office at the village level. Implications: Successful E-Office integration requires addressing human resource competency and enhancing officer disposition through mandatory training and committed leadership. Highlights: E-Buddy implementation is hindered by limited officer capability and operational mastery. Low officer commitment (Disposition) is a primary barrier to E-Office success in village administration. Bureaucratic structure supports E-Buddy, but lack of specific SOPs for letter processing remains a constraint. Keywords: Implementation, Administrative Management, E-Buddy, Grindle's Model, Officer Capability